Characterising amylase gene CNVs and application to association studies - Shwan, Nzar Ali Ameen (2018)
The human amylase gene family on chromosome 1p21.1 is highly copy number variable. The salivary (AMY1) and pancreatic (AMY2A and AMY2B) amylase genes encode the starch-digesting enzymes expressed in the salivary gland and pancreas, respectively. Different molecular approaches have been used to investigate copy number variation (CNV) in this region, more specifically the salivary AMY1 copy number (CN). High AMY1 CN has been shown to be correlated with adaptation to human dietary starch intake, and low AMY1 CN reported to be a predisposition factor to obesity. These findings have not been replicated independently, and reliable measurement methods and accurate structural characterisation of the region are important to address such findings. The large dynamic copy number range of AMY1 genes and the extent of sequence identity in this region demands accurate, reliable and high-throughput CNV measurement methods. In this study, high-resolution paralogue ratio test (PRT) measurement methods have been developed to define the full scope of variations in human amylase genes. The data demonstrated independent allelic series of amylase CN variants (CNVs) in sub-Saharan Africans, in which the region has undergone homologous and non-homologous rearrangements to create new haplotypes, some of which contain five copies each of the AMY2A and AMY2B genes. These expansions have taken AMY2B/AMY2A /AMY1 repeat unit as a starting point to create new allelic series represented by triplication, quadruplication and quintuplication. With a better understanding of amylase region variation and the high-resolution measurement methods developed in this study, the effect of amylase CNVs on diseases was assessed in eight common diseases. The results of case-control association studies showed no evidence of significant association between amylase CNVs and the eight diseases being tested. Furthermore, the significant association between amylase CN and body mass index (BMI) has been reassessed in three different cohorts (in a total of 4237 samples). The data demonstrated no evidence for an association between amylase CNVs and BMI. The lack of evidence of significant associations suggest that amylase CNVs does not influence BMI or obesity.